Implication of Insecurity on Higher Education in South-East Geo-Political Zone of Nigeria and Way Forward - Niyi Jacob Ogunode; Conrad Ugochukwu Ukozor (Researchparks Publishing, 2022)
This paper discussed implication of insecurity challenges on the higher institutions in the south-east geo-political zone. Secondary data and primary data were used to provide empirical support to some of the points raised in the paper. The paper concluded that disruption of higher education administration, teaching programme, research programme, community service programme, academic calendar, academic programme accreditation, and suspension of infrastructural facilities projects, brain-drain and reduction of academic staff’ strength are the impact of insecurity on higher education in south east geo-political zone and the paper recommendation that the federal and state government should address issues responsible for the high rate of insecurity in the region.